Green hydrogen: water use implications and opportunities. Issue 12 (December 2021) - Newborough, Marcus; Cooley, Graham
Abstract : Substituting green hydrogen for conventional fuels will serve to decarbonise the energy system and reduce its water consumption. Benefits will also accrue for the water sector, including improving the efficiency of wastewater treatment, oxygenating hypoxic water bodies, improving the provision of drinking water supplies in arid regions, and making better use of the seawater resource. Accordingly it is recommended that national 'net zero' strategies address renewable electricity, green hydrogen and water use in a more integrated manner.